CLOSING THE ACTIVITIES OF CLASSIC POETS TYPOLOGICAL PROPERTIES OF PUBLICATIONS - Kalekeev Kuanyshbay Jartybaevich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article explores the typological features of publications covering the activities of artists, the specific principles of coverage of the life and work of Karakalpak artists in the press and the skills of publicists and journalists in communicating this topic to the general public through the media.